Density versus biomass responses of zooplankton to environmental variability in a subtropical shallow lake. Issue 1 (2nd January 2021) - Morais da Rosa, Luana; Cardoso, Luciana de Souza; Rodrigues, Lucia Ribeiro; da Motta-Marques, David
ABSTRACT: Density and biomass are commonly used in ecological studies of zooplankton. However, these metrics are not functionally equivalent and provide different information regarding community structure. Differences in the response of zooplankton, as estimated through both density and biomass in relation to environmental variability, were investigated in a large subtropical lake. Results based on 2 years of seasonal sampling at 9 points in Lake Mangueira (southern Brazil) showed a large difference in the pattern of dominance of zooplankton between the density and biomass metrics. Ciliates composed >58% of zooplankton density (rotifers 29.4%) but only 16.1% of zooplankton biomass. Analyzing the composition of zooplankton based only on biomass might therefore underestimate the importance of microzooplankton components, which are an important trophic link in pelagic food webs of subtropical systems. The differences between the 2 metrics in relation to abiotic variables were assessed through redundancy analysis. Seasonality was the main factor driving the variability of zooplankton, and density proved to be the best metric to show the seasonal variation of zooplankton taxa and taxonomic groups in relation to environmental conditions. Density was also the most appropriate metric for analyzing annual cycles and the seasonal succession of species. However, the biomass metric was significantly related to production-related parameters (pH and chlorophyll a ) and was essential to better understand zooplankton grazing relationships and the trophic structure of the system.